(untitled) (Polish Yearbook of International Law, 2023)
One of the major conflicts between populist and non-populist forces (movements, parties, governments) as well as the European Union (EU) institutions has manifested in the area of immigration policy. This article investigates how the influx of migrants in 2015-2016 was subsequently used by populists as a policy conflict ground within the EU. In this context, it particularly looks at how the problem of migration was framed and map the policy responses in the selected EU Member States. The article covers the 2015-2018 period and includes the following countries: France, Germany, Greece, Italy, Hungary, and Poland. The article observes that the 2015-2016 migration crisis and the response to it led to (or reinvigorated existing) politicisation of the topic across the EU, forcing the parties from all sides of the political spectrum to take a position on it. Simultaneously, one may also observe a process of securitisation of migration in the political debate in all analysed countries. Irregular migration was construed as a security threat by many political parties and leaders, requiring emergency measures and justifying actions outside the normal bounds of political and legal procedures. While the securitisation strategy was most visible in the discourse of the right-wing populist parties, its elements were progressively taken by the mainstream parties, arguably in response to increased salience of the issue. The article also finds a correlation between the ideological profile of the parties and their approach to the migration crisis and the proposed EU response. All the parties located close to the right extreme tended to take a strong anti-immigration and anti-EU stance. All of them also ranked high in the populist index. On the other hand, the populist parties located on the left side or in the centre of the political spectrum took a moderate stance on this issue.